Main‐Side Chain Hydrogen Bonding‐Based Self‐Healable Polyurethane with Highly Stretchable, Excellent Mechanical Properties for Self‐Healing Acid–Base Resistant Coating. Issue 20 (2nd September 2021) - Xu, Heng; Tu, Jing; Li, Pingyun; Liang, Li; Ji, Jie; Xiang, Guifeng; Li, Haozhe; Zhang, Yang; Guo, Xiaode
Abstract: Developing an autonomous self‐healing polyurethane (PU) elastomer with excellent mechanical properties and high ductility has attracted increasing attention. Nowadays, the synthesis of elastomers with excellent mechanical properties and rapid self‐healing at room temperature faces a huge challenge. Herein, This work reports a new supramolecular PU with excellent mechanical properties and rapid self‐healing at room temperature through the introduction of T‐type chain extender into the supramolecular polymer chain. The introduction of T‐chain extender can be used to enhance the mechanical strength of PU, and the multiple hydrogen bonds on the side‐chain provide theoretical support for the rapid self‐healing ability of PU. Maximum stress of the synthesized PU can reach 3.4 ± 0.15 Mpa, and maximum elongation at break can reach 3200% ± 160%. Due to flexibility and re‐constructability of side‐chain hydrogen bonds, PU stress repair efficiency can reach 96.7%, and can be self‐healing scratches rapidly and effectively at room temperature. The mechanical properties and self‐healing properties of PU can be adjusted by the content of T‐type chain extender. The PU is applied to the metal surface coating, which has excellent acid–base resistance, bond strength up to 2.9 ± 0.1 Mpa, and the ability to eliminate local damage on the coating surface quickly at room temperature. Abstract : Based on the principle of main‐side chain hydrogen reconstruction, polyurethanes (PUs) areprepared with self‐healing properties. The PU material has excellent stress heal ability and local scratch elimination function. The PU material is applied to the metal surface coating to test the acid–base resistance and self‐healing. The results show that the coating has excellent acid–base resistance and self‐healing properties.